A capture-recapture technique to estimate the size of the injecting drug user population attending syringe exchange programs: AjUDE-Brasil II Project - Sueli Aparecida Mingoti; Waleska Teixeira Caiaffa
This paper presents the results of a study with a two-occasion capture-recapture design. The data are part of the AjUDE-Brasil II Project, carried out in 2000-2001. Estimation of the size of the IDU population attending a syringe-exchange program (SEP) in São José do Rio Preto, Salvador, and Porto Alegre, Brazil, was performed using Chao's model. Capture probabilities were also estimated. For Porto Alegre a comparison of the results from the AjUDE-Brasil I and AjUDE-Brasil II Projects was performed. Results are also presented for error rates secondary to the choice of matching criteria.